Floral ultrastructure of two Brazilian aquatic-epiphytic bladderworts: Utricularia cornigera Studnička and U. nelumbifolia Gardner (Lentibulariaceae) - Płachno, Bartosz J.; Stpiczyńska, Małgorzata; Davies, Kevin L.; Świątek, Piotr; de Miranda, Vitor Fernandes Oliveira [UNESP] (Springer Nature, 2017)
Utricularia cornigera and Utricularia nelumbifolia are giant, aquatic-epiphytic species of carnivorous bladderwort from southeastern Brazil that grow in the central ‘urns’ of bromeliads. Both species have large, colourful flowers. The main aim of our study is to ascertain whether the prominent floral palate of U. cornigera and U. nelumbifolia functions as an unguentarius—i.e. an organ that bears osmophores. Floral tissues of both species were investigated using light microscopy, scanning electron microscopy, transmission electron microscopy and histochemistry. Floral palates of U. cornigera and U. nelumbifolia provide clear visual signals for pollinating insects. In both species, the palate possesses diverse micro-morphology, comprising unicellular, conical to villiform papillae and multicellular, uniseriate, glandular trichomes that frequently display terminal branching. The most characteristic ultrastructural feature of these papillae was the presence of relatively large, polymorphic plastids (chromoplasts) containing many plastoglobuli. Similar plastids are known to occur in the fragrance-producing (osmophores) and oil-producing (elaiophores) tissues of several orchid species. Thus, these palate papillae may play a key role in providing the olfactory stimulus for the attraction of insect pollinators. Nectariferous trichomes were observed in the floral spurs of both species, and in U. nelumbifolia, free nectar was also recorded. The location, micro-morphology, anatomy and ultrastructure of the floral palate of the two species investigated may thus indicate that the palate functions as an unguentarius. Furthermore, the flowers of these taxa, like those of U. reniformis, have features consistent with bee pollination.
Keywords: Bladderwort; Carnivorous plant; Floral micro-morphology; Lentibulariaceae; Osmophore; Palate; Pollination; Sect. Iperua; Ultrastructure